A new form of discrete real Fourier transform and its potential applications - Grzegorz Plewa (Annals of Mathematics and Physics - Peertechz Publications, 2022)
The paper will present a new version of a real discrete Fourier transform, based on a symmetric frequencies combination of sine and cosine functions. Basic aspects of the construction as well as the potential applications will be discussed. This will include elements of the standard Fourier analysis as well as applications to the class of differential equations in string theory.